(untitled) (Global Journal of Human-Social Science, 2021)
The committee s commitments to visit basic school in the Assin community to strengthen good health led to the discovery of JHS 1 pupils misconceptions about the concept of malaria Mr Charles Nuamah the WASH committee chairman and Miss Ruby Jecty the secretary both of Foso College of Education observed Miss Linda Kwofie a student teacher on establishing teaching go through a hectic time facilitating the causes and prevention of malaria Despite the striking information on Malaria discussed with the learners these JHS 1 learners did not make the attempt to understand the concept of malaria taught in the school because of some superstitious beliefs about the disease held religiously in the community As malaria threatens human health and WASH has health component as its focus the authors saw it as a responsibility to research on Malaria and collate the information into a learner friendly package accompanied by appropriate strategies to challenge these misconceptions Action research design which concerns itself with investigating challenges faced by a group of people and finding immediate resultant strategies to remedy them informed the use of purposive sampling and census techniques to involve all twenty eight JHS 1 learners